Using Digital Classroom Management to Engage and Foster Collaboration Among Accounting Students - Laily, Nujmatul; ., Sulikah (KnE Social Sciences, 2024)
This research is motivated by the low involvement and participation of students in learning which is caused by the lack of attractive learning media used by lecturers. The increasing popularity of digital classroom management-based learning media motivated the research. This research aims to develop learning media based on digital classroom management (ClassDoJo). This research is categorized as research and development, namely research that aims to produce certain products and test their effectiveness. This research focuses on developing digital classroom management (ClassDojo)-based learning media for accounting teaching material development courses. This research uses the ADDIE development model popularized by Dick and Carey (1996) which consists of five important stages, namely analyze, design develop, implement, and evaluate. The result shows that the learning media is feasible to use in learning. Keywords: ClassDojo, learning media, digital classroom